Penerapan Lean Warehouse Pada Gudang Produk Jadi Untuk Meminimasi Pemborosan (Studi Kasus: CV Bumi Makmur, Karangtengah, Wonogiri) - Musfiroh, Febriana; , Ida Nursanti, ST., M.Eng.Sc (2016)
The development of the business requires companies must constantly improve their performance so as to compete with other companies in the domestic and international markets. Improved performance of the company should be carried out continuously on all lines of production processes in order to minimize the waste that occurs by the application of lean warehouse. The research was conducted at CV. Bumi Makmur in the warehouse 1 and 2, there are three work stations namely mixing stations, packing stations and storage station. The purpose of this research was to determine what types of waste are contained in the warehouse, identify, analyze, and reducing waste in warehousing process that has the highest value. Big Picture Mapping is used to visually map a information flow and the physical flow existing system up to end consumer. Distributing quisioner to know the opinion of stakeholders in the warehouse regarding which waste must be eliminated first. Obtained waste with the highest score is waste overproduction in warehouse 1 and waste of defects in warehouse 2, then which will identified the cause of the problem using a fishbone diagram. To minimize the waste that occurs repairs to carry out the implementation of 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke), after implementation of 5S is obtained good results, the results of inspection is reduction of mismatch of Red category were 13 mismatch to White as much as 3 mismatch. Then measuring of flow processes time in the warehouse after implementation of 5S is obtained time reduction is 3 hours 10 minutes 35 seconds.